Perlindungan Hukum terhadap Anak Sebagai Korban Pedofilia dalam Perspektif Viktimologi - Rr. Britamia Rachel Ekklesia (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Child sexual abuse constitutes a serious violation of human rights that causes long-term physical, psychological, and social consequences for victims. Legal protection for child victims should not merely focus on punishing offenders but must also ensure the fulfillment of victims' rights to rehabilitation, restitution, and comprehensive recovery. This study aims to analyze legal protection for child victims of pedophilia from a victimological perspective through an examination. This research employs normative legal research using statutory, conceptual, and case approaches. Legal materials were collected through library research consisting of legislation, court decisions, legal doctrines, and scholarly articles. The findings reveal that the court provided retributive legal protection by imposing imprisonment, fines, and chemical castration on the offender. Nevertheless, the judgment failed to accommodate victims' recovery rights because it did not order psychological rehabilitation or restitution as mandated under Indonesian child protection and sexual violence legislation. From a victimological perspective, the child experienced primary victimization as a direct consequence of the offense and remains vulnerable to secondary victimization due to inadequate post-trial recovery mechanisms. Therefore, legal protection should prioritize both offender punishment and comprehensive victim recovery to achieve substantive justice for child victims.